Toxic action of phosphine on the adults of copra mite Tyrophagus putrescentiae [Astigmata : Acaridae] - Jian, F.; Jayas, D.S.; White, N.D.G. (Phytoprotection)

(untitled) (Société de protection des plantes du Québec (SPPQ)l, 2000)
The inhibitory effects of phosphine gas on cytochrome C oxidase and catalase, both in vivo and in vitro, and gas uptake by adults of Tyrophagus putrescentiae were determined. The activities of both enzymes were reduced by the gas. Relative inhibition rates of the enzymes were : in vivo catalase > in vitro catalase, in vivo cytochrome C oxidase < in vitro cytochrome C oxidase, and the inhibition effects of in vitro enzymes were proportional to the exposure period of phosphine applied to the cytosolic extracts. Although the uptake of phosphine by adults increased with an increase of phosphine concentration and exposure period, the rate of uptake was relatively slower than at low concentration and short exposure period. The absorption mechanism of phosphine between insects and mites appears to be different.